Rebalancing growth in the Republic of Korea - Joonkyung Ha; Jong-wha Lee; Lea Sumulong (Asian Development Bank Institute (ADBI), 2010)
The current account surplus of the Republic of Korea (henceforth Korea) increased significantly in the immediate recovery period after the 1997 - 1998 Asian financial crisis. Since then the surplus has gradually diminished, and from 2006 to 2008, the current account was close to being balanced. Econometric analysis reveals that the effect of exchange rate changes on Korea's trade is not robust during non-crisis periods. Exchange rates only significantly affect trade when observations during crisis periods are included. This suggests that exchange rate adjustments alone will not solve the imbalance issue. Korea's external imbalances are not only caused by external factors; they also reflect internal and policy factors such as: (i) saving-investment imbalances; (ii) export-oriented policies; and (iii) the unbalanced structure of manufacturing and services. These internal imbalances result from domestic distortions and structural imbalances arising from market inefficiencies and public policies. These must be addressed to ensure balanced and sustained economic growth.
Keywords: E2; E6; F4; O1; O2; 330; Zahlungsbilanzungleichgewicht; Exportinduziertes Wachstum; Wachstumspolitik; Südkorea